Dream characteristics in a Brazilian sample: an online survey focusing on lucid dreaming - Mota-Rolim, Sérgio A.; Targino, Zé H.; Souza, Bryan C.; Blanco, Wilfredo; Araujo, John F.; Ribeiro, Sidarta (Frontiers in Human Neuroscience, 2013)
During sleep, humans experience the offline images and sensations that we call dreams, which are typically emotional and lacking in rational judgment of their bizarreness. However, during lucid dreaming (LD), subjects know that they are dreaming, and may control oneiric content. Dreaming and LD features have been studied in North Americans, Europeans and Asians, but not among Brazilians, the largest population in Latin America. Here we investigated dreams and LD characteristics in a Brazilian sample (n=3,427; median age=25 years) through an online survey. The subjects reported recalling dreams at least once a week (76%). Dreams typically depicted actions (93%), known people (92%), sounds/voices (78%), and colored images (76%). The oneiric content was associated with plans for the upcoming days (37%), memories of the previous day (13%), or unrelated to the dreamer (30%). Nightmares usually depicted anxiety/fear (65%), being stalked (48%), or other unpleasant sensations (47%). These data corroborate Freudian notion of day residue, and suggest that dreams are simulations of life situations that are related to our psychobiological integrity. Regarding LD, we observed that 77% of the subjects experienced LD at least once in life (44% up to 10 episodes ever), and for 48% LD subjectively lasted less than 1 minute. LD frequency correlated weakly with dream recall frequency (r=0.20, p<0.01), and LD control was rare (29%). LD occurrence was facilitated when subjects did not need to wake up early (38%), a situation that increases REMS duration, or when subjects were under stress (30%), which increases REMS transitions into waking. These results indicate that LD is a relatively ubiquitous but not frequent state, being unstable, difficult to control, and facilitated by increases in REMS duration and transitions to wake state. Together with LD incidence in USA, Europe and Asia, our data from Latin America strengthen the notion that LD is a general phenomenon of the human species.